Certain Concepts of Vague Graphs With Applications to Medical Diagnosis - Shao, Zehui; Kosari, Saeed; Shoaib, Muhammad; Rashmanlou, Hossein (Frontiers in Physics, 2020)
Graphs are among the more ubiquitous models of natural and human-made structures. They are used to model with various categories of relations and process dynamics in biological and social systems. A vague graph has numerous applications in the fields of geometry and operational research. It has been a useful scope in various fields of computer science. In this paper, our important purpose of the study is to describe properties rejection, maximal product, symmetric difference and residue product of vague graphs which have been deeply discussion with different examples and moreover, we investigate some of their other related properties. We also presented the applications of vague set in medical diagnosis.